2017
DOI: 10.12991/mpj.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adenovirus activity, antioxidant potential, and phenolic content of dried flower buds of Syzygium aromaticum extract in HEp2 cell line

Abstract: The aim of this study is to evaluate in vitro anti-adenovirus property, antioxidant potential, and total phenolic content of dried flowers buds of Syzygium aromaticum crude extract. The crud extract was prepared and its anti-adenovirus activity was investigated on HEp2 cell line using MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, Folin-Ciocalteu method and aluminum chloride colorimetric method was used to determine antioxidant activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The most important combination that has been shown to have antiviral and antibacterial is Phenolic which in the results of this study proved that Melissa officinalis have a high level of these compounds. 80 Inhibition of viral replication Allahverdiyev et al, 21 Mazzanti et al 62 Inhibition of protein synthesis for replication and reduced viral infectivity in cells with melissa volatile oils (sitral and sitronellal)…”
Section: Adenovirusmentioning
confidence: 99%
See 3 more Smart Citations
“…The most important combination that has been shown to have antiviral and antibacterial is Phenolic which in the results of this study proved that Melissa officinalis have a high level of these compounds. 80 Inhibition of viral replication Allahverdiyev et al, 21 Mazzanti et al 62 Inhibition of protein synthesis for replication and reduced viral infectivity in cells with melissa volatile oils (sitral and sitronellal)…”
Section: Adenovirusmentioning
confidence: 99%
“…Therefore, it is important to find an effective medicine. Moradi et al 80 showed that the extract of Melissa officinalis works after the penetration of adenovirus into the cell and leaves its effect. Figure 2 summarizes the antiviral effects of Melissa officinalis…”
Section: Adenovirusmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant capacity of the extracts was evaluated using a tweaked version of the method developed by Moradi et al 11 . A hydroethanolic solution of DPPH (3.4mg/100 mL) was added to a 50 L aliquot of the sample solutions to determine their concentrations (25-400 g/mL).…”
Section: Dpph (2 2-diphenyl-1-picrylhydrazyl) Free Radical Scavenging...mentioning
confidence: 99%